Antioxidative metabolites synthesized by marine pigmented vibrio sp and its protection on oxidative deterioration of membrane lipids - Pawar, Ravindra; Mohandass, Chellandi; Dastager, Syed Gulam; Kolekar, Yogesh M.; Malwankar, Rahul (Applied Biochemistry and Biotechnology, 2016)
Bacterial strain Vibrio sp. (PIGB 184) isolated from water samples of the Arabian Sea and identified through 16S rRNA demonstrated the production of pigmentary antioxidants with higher ABTS activities 90.9 +/- 0.42 % in comparison with the standard commercial pigmented antioxidant, quercetin 88.8 +/- 1.4 %. Antioxidative metabolites of this strain substantially inhibit the lipid peroxidation (LPO) reactions tested in sheep liver and brain. The antioxidant compounds produced by the Vibrio sp. (PIGB 184), analysed by GC-MS, reveals that it is composed mostly of phenol, 2,4-bis(1,1-dimethylethyl) and pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro-3-(2-methylpropyl). The interrelationship assessed between LPO and the phenolic compounds showed significant correlation with anti-LPO properties (R (2) = 0.9698 to 0.9861). These compounds are responsible for obstruction of harmful radical associated biochemical reactions in biological systems. Pigmented metabolites also tested for attributive biological properties against pathogenic bacteria showed prominent inhibition towards Gram-positive organisms (31.25 to 62.5 mu g ml(-1)). From this study, it may be suggested that the marine bacterium PIGB 184 could be used as a potential bio-resource for antioxidants and needs to be worked out for mass production.
Keywords: Antioxidants; Lipid peroxidation; Marine pigmented bacteria; Pathogen inhibition; Phenolics